Acoustic Emission Control of Compounds with Interference, Which Are Assembled by Thermal Method - Zenkin Mykola; Lisovets Serhii; Makatora Dmytro; Kosiba Ján (Acta Technologica Agriculturae)
Acoustic emission control means for tension connections are proposed. The features of the contact zone, such as the gas gap between the shaft and the bushing and the penetration of microroughnesses of the shaft surface into the bushing surface, are considered. It is shown that the main indicator of such compounds is total acoustic emission. It has been established that with increasing tension, the maximum intensity of acoustic emission signals is observed earlier, and their amplitude becomes larger. In addition, it has been found that total acoustic emission depends on the strength of joints and the magnitude of total acoustic emission can determine this strength. The paper presents the results of studies of several series of experimental and field samples. It has been established that the greater the intensity of acoustic emission signals and the lower the total acoustic emission, the stronger the tension bonds. It has been established that there is no direct relationship between the intensity of acoustic emission signals and the contact surface area, but with an increase in the contact area, total acoustic emission also increases.